PEMBUATAN SISTEM OTOMASIUNTUK PENGATURAN MEKANISME KERJA MESIN CETAK KERUPUK MENGGUNAKAN MIKROKONTROLER ATMega - Sukendar, Aang; Martinus, .; Tanti, Novri (Jurnal Ilmiah Teknik Mesin FEMA, 2013)
Developments in science and technology has increased very rapidly. One is the industrial field. At home industry (home industry) required a more sophisticated production system in order to maximize production. Engine control system working mechanism of crackers is an idea to create an automated system on a machine that makes in terms of operation. Has created a working mechanism controlling printing using Microcontroller ATMega 16 crackers. The system uses a microcontroller to control the relay drivers to switch on or switch off the AC motor. Optocoupler sensors and limit switches as an input to set the working mechanism of the machine automatically.The test results show that the driver relays are used to control the mechanism of action machine can work well. Similarly optocoupler sensor and AC motors as propulsion machinery.Keywords: Home industry, printing machines crackers, driver relay, optocoupler, limit switch, microcontroller.